Morphological, physiological and skating performance profiles of male age-group elite ice hockey players - Allisse, M.; Sercia, P.; Comtois, A.-S.; Leone, M. (Journal of Human Kinetics, 2017)
The purpose of this study was to describe the evolution of morphological, physiological and skating performance profiles of elite age-group ice hockey players based on repeated measures spread over one season. In addition, the results of fitness tests and training programs performed in off-ice conditions and their relationship with skating performance were analyzed. Eighteen high level age-group ice hockey players (13.1 ± 0.6 years) were assessed off and on-ice at the beginning and at the end of the hockey season. A third evaluation was also conducted at the beginning of the following hockey season. The players were taller, heavier, and showed bone breadths and muscle girths above the reference population of the same age. Muscular variables improved significantly during and between the two hockey seasons (p < 0.05). However, maximal aerobic power improved only during the off-season. All skating performance tests exhibited significant enhancements during the hockey season, but not during the off-season where some degradation was observed. Finally, weak observed variances (generally <20% of the explained variance) between physiological variables measured off-ice and on-ice skating performance tests indicated important gaps, both in the choice of the off-ice assessment tools as well as in training methods conventionally used. The reflection on the best way to assess and train hockey players certainly deserves to be continued.